KERJASAMA GURU DAN ORANG TUA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS 1 B MADRASAH IBTIDAIYAH SWASTA AL-HIKMAH SIDANG TAHUN PELAJARAN 2022-2023 - Rety Adhariyanti; Parni; Hadisa Putri (Pondok Pesantren Baitul Qur`an Sambas, 2024)
This research discusses about collaboration between teachers and parents to improve student learning outcomes in class 1 B of MIS Al-Hikmah Sidang for the 2022-2023 academic year. This research has two objectives, namely: 1) To find out how teachers and parents collaborate to improve student learning outcomes in class 1 B of MIS Al-Hikmah Sidang for the 2022-2023 academic year; 2) To find out student learning outcomes from collaboration between teachers and parents of class 1 B MIS Al-Hikmah Sidang for the 2022-2023 school year. This research uses a qualitative approach and descriptive research type. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data collection, data reduction, data presentation and drawing conclusions. The data validity checking technique uses triangulation and member check. The research results show that: 1) Student learning outcomes from collaboration between teachers and parents in class 1 B of MIS Al-Hikmah Sidang can be seen from three aspects, namely: cognitive, affective and psychomotor aspects. 2) Forms of collaboration between teachers and parents to improve student learning outcomes in class 1 B MIS Al-Hikmah Sidang consisting of: a) parenting, b) communication, c) volunteering, d) studying at home, e) joint decision making, f ) collaborating with the community, g) home visits.